Production of Writing and Printing Papers from Prosopis juliflora - Guha, S. R. D.; Gupta, R. K.; Mathur, G. M.; Sharma, Y. K. (Indian Forester, 1970)
Proximate chemical analysis and fibre dimensions of Prosopis juliflora have been recarded. Bleached sulphate pulps have been prepared on the laboratory scale. Laboratory acale experiments were confirmed on pilot plant scale. Laboratory as well as pilot plant scale expetiments have shown that writing and printing papers can be produced by Prosopis juliflora. As the wood was very crooked difficulties were observed in chipping.